Shia Doctrine Contrasted with Islam - Marsheila, Naura (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2021)
The emergence of "Shia" teachings, namely a new sect in Islam and the science of anthropology that has been paid attention to. This Islamic study is usually interpreted theologically. This understanding is underdeveloped in Islamic scholarship and makes it impossible for Muslims to carry out self-imposed religious practices. This article aims to explain the relationship between anthropology and a doctrine that is considered very different from that applied to Islamic studies, namely the doctrine of "Shia teachings" which does not provide freedom for people who bring in new Islamic schools and teachings. not conducive to the welfare and success of Muslims. in spreading his message. To further advance this research, we want to conclude that the anthropological approach makes an active contribution to the spread and development of Islamic religious studies.